Assessment of kiwifruit firmness by using airflow and laser technique. Issue 2 (9th February 2023) - Sun, Qinming; Luo, Xiuzhi; He, Ke; Jing, Bowen; Tang, Xiuying
Abstract: Firmness is a valid and widely acknowledged indication of fruit quality that is directly connected to physical structure and mechanical qualities. The deformation signals of kiwifruit for firmness assessment were acquired using an assessment system based on airflow and laser technology in this investigation. Using partial least squares regression (PLSR), genetic algorithm optimization of bp neural network (GA‐BP), and an extreme learning machine (ELM), deformation data from kiwifruit was used to create models of Magness–Taylor penetration firmness prediction. The ELM model outperformed the PLSR model, and GA‐BP model in the prediction set, with a correlation coefficient of 0.876 and a root mean squared error of 3.576 N in the prediction set. These findings showed that an assessment system based on airflow and laser techniques can be utilized to assess the firmness of kiwifruit quickly and nondestructively.